Examining Educators' Proficiency in Recognizing Learning Preferences of Young Learners to Facilitate Tailored Instruction in Early Childhood Education - Mailatul Muyassaroh; Hilda Pradina Faradiba; Aditya Syaiful Dhuhri (Global Education : International Journal of Educational Sciences and Languages, 2024)
This research investigates educators' ability to identify young children's learning preferences to facilitate personalized learning in early childhood education. Through this study, we explore the extent to which educators can recognize diverse learning styles and implement learning strategies that suit children's individual needs. This case study focuses on the implementation of an independent curriculum at Unesa 1 Labschool Kindergarten as a framework for analyzing educators' efforts to support differentiated learning for each child.